The graffiti of Mohamed Mahmoud and the politics of transition in Egypt: The transformation of space, sociality and identities - El-Hawary, Nouran Al-Anwar (AUC Knowledge Fountain, 2014)
This study is concerned with the spatial transformations taking place in Mohamed Mahmoud that branches from Midan el-Tahrir; the official site of the Egyptian January 25 Revolution. Since the revolution, this street has witnessed a great deal of violence during several bloody clashes between protesters and security forces. It has also become famous for the dissenting graffiti murals wrapping the walls of it entrance. By conducting ethnography of this block of Mohamed Mahmoud Street, my study focuses on the residents and shop owners in the area, who I frame as the graffiti's ‘unintended audience,’ to understand how these spatial and political transformations have affected this space, the residents’ experience, social relations and sense of belonging. I argue that these new spatial transformations brought by the revolution have introduced an alternative public space, inviting a peculiar array of incidents and distinctive social interactions in which people deploy the mode of speaking in their subversion of many ambivalences in the course of troubled political transition.